Investigation of transformation process of 1,3-diphenylguanidine in disinfection water treatment - Ying, Lebing (Nanyang Technological University, 2024)
Tire wear products (TWPs) potentially pose risks to human health and the environment when introduced into surface water cycle. Among all TWPs, 1,3-diphenylguanidine (DPG), a widely used vulcanization accelerator in the rubber industry, has gained increasing attention recently with high concentrations identified in the environment. To compare and comprehend the disinfection process of DPG, this work investigates (1) the effects of multiple disinfection methods towards DPG; (2) the reaction kinetics of DPG during monochloramination; (3) toxicity and bioenergetics of DPG disinfection products based on in vitro experiments; (4) transformation products (TPs) of DPG during chlorination and monochloramination. It has been revealed that DPG is insensitive in regards of UV alone, and that UV has neglecting effect on promoting the effect of chlorine and monochloramine effectively when degrading DPG. Additionally, the reactivity of monochloramine is significantly slower compared to chlorination of DPG, with the maximum efficiency observed at pH 7 to pH 8. While chlorination effectively degrades DPG, this process leads to the formation of transformation products (TPs) like nitrosamines, notably nitroso-dimethylamine (NDMA). NDMA, a significant byproduct closely linked with vulcanization agents used in tire manufacturing, is known for its potential toxicity. In contrast, monochloramination can generally resulted in lower concentrations of trihalomethanes (THMs), haloacetic acids (HAAs), and total organic halogen (TOX) compared to chlorination. Following this, bioassays were conducted on the DPG TPs generated treated by chlorine and NH2Cl. An interesting outcome was found in cytotoxicity testing that that cytotoxicity hierarchy is as follows: chlorine TPs > monochloramine TPs > DPG. Moreover, oxidant-to-DPG molar ratios 10 and 20 lead to maximum cytotoxicity in both chlorination and monochloramination. Additionally, bioenergetics experiments demonstrate that chlorine and monochloramine disinfection by-products induce mitochondrial dysfunction and enhance glycolytic function in HepG2 cells. The genotoxic response from p53 cells further indicated the genotoxic effects of certain disinfection products. The variation of bioassay experiments has led to the the, analysis of TPs using high-resolution mass spectrometry (HRMS) which identifies ten TPs, with chlorination yielding more TPs than monochloramination. Generally, a chlorine or monochloramine molar ratio to DPG of 10-20 results in an increased formation of TPs and heightened cytotoxicity. Notably, higher oxidant molar ratios increased the formation of monoguanidine TPs and DPG hydroxylation during chlorination, whereas monochloramination lead to DPG substitution predominantly generating chlorinated DPG due to weaker oxidation effects. It has been assumed that some identified TPs like DPG-119, might contribute most toxicity in chlorine 100 μM and chlorine 500 μM groups. These findings provide valuable information for the appropriate treatment of DPG and disinfection processes in water facilities to mitigate potential risks to human health and the ecosystem.